A checklist for appraising the reporting and methodological quality of menstrual cycle (ARMQ-MC) phase-based research in sport science - Elliott-Sale, K. J.; Hecksteden, A.; Wilke, C. F.; Okholm Kryger, K.; Nimphius, S. (Science and Medicine in Football, 2026)
The recent, welcomed growth in women`s football (i.e., research, participation, investment, coverage, etc.) means that robust data and credible messaging are needed to support the health and performance of women football players (The Football Association Citation2022; Okholm-Kryger et al. Citation2022; Women`s Sport Trust Citation2024; FIFA Citation2024). Historically, women have been marginalised in football research. Clausen et al. (Clausen et al. Citation2025) showed that from the 722 studies in elite football, involving 98,777 participants, only 7% were women and from the 104 studies involving women, only four (<4%) provided sufficient information to define menstrual status. Moreover, in many sports and medicine-related academic degrees, women are siloed into a `special population`, with female-specific topics such as the menstrual cycle barely covered in the curriculum, if at all. Collectively, this contributes to: (i) a lack of knowledge and high-quality data on female-specific football and sport science topics; (ii) a gap in training of researchers to conduct high-quality studies in this space; and (iii) a low number of reviewers of scientific journals with expertise in these topics.